2022
DOI: 10.1097/md.0000000000032034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of warm acupuncture in the treatment of type 2 diabetic kidney disease: A protocol of a randomized controlled trial

Abstract: Background: Type 2 diabetic kidney disease (DKD) is one of the most common and harmful chronic complications in clinical practice, and there is no reliable and targeted treatment plan at present. As a classic complementary and alternative therapy, evidence have shown that warm acupuncture has advantages in the treatment of type 2 DKD. However, there is still a lack of high-quality and long-term follow-up randomized controlled trials of warm acupuncture in the treatment of type 2 DKD. Methods: This is a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…DKD manifests as hyperfiltration and proteinuria in the early stage and end-stage renal disease in the late stage ( 3 ). Epidemiological studies have shown that the number of patients with DKD is increasing year by year, and it is estimated that there will be 592 million patients with DKD by 2035, accounting for about 8%–10% of the global population ( 4 , 5 ). Renal failure in patients with advanced DKD often requires renal replacement therapy or renal transplantation, which seriously jeopardizes the physical and mental health of patients and imposes a substantial economic burden on families and society ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…DKD manifests as hyperfiltration and proteinuria in the early stage and end-stage renal disease in the late stage ( 3 ). Epidemiological studies have shown that the number of patients with DKD is increasing year by year, and it is estimated that there will be 592 million patients with DKD by 2035, accounting for about 8%–10% of the global population ( 4 , 5 ). Renal failure in patients with advanced DKD often requires renal replacement therapy or renal transplantation, which seriously jeopardizes the physical and mental health of patients and imposes a substantial economic burden on families and society ( 6 ).…”
Section: Introductionmentioning
confidence: 99%